Q-switched Erbium-doped Fiber Laser with a Black Phosphorus Saturable Absorber - Razak, Nurul Nadia; Latiff, Anas Abdul; Zakaria, Zahriladha; Harun, Sulaiman Wadi (Photonics Society of Poland, 2017)
A passively Q-switched Erbium-doped fiber laser (EDFL) is demonstrated using a black phosphorus saturable absorber as the Q-switcher. The laser generates a stable pulse operating at a wavelength of 1562.35 nm within a pump power region from 7.2 mW to 42.3 mW. At a 980 nm pump power of 42.3 mW, the EDFL generates an optical pulse train with a repetition rate of 44.72 kHz and pulse width of 9.8 μs. The maximum pulse energy of 81.5 nJ is obtained at a pump power of 35.2 mW. A higher performance Q-switched EDFL is expected to be achieved with the optimization of the saturable absorber and laser cavity.